Research in Mathematics Education in Australasia 2012-2015 - Makar, Katie; Dole, Shelley; Visnovska, Jana; Goos, Merrilyn; Bennison, Anne; Fry, Kym (Springer Nature Singapore : Imprint: Springer, 2016)
With the ninth edition of the four-yearly review of mathematics education research in Australasia, the Mathematics Education Research Group of Australasia (MERGA) discusses the Australasian research in mathematics education in the four years from 2012-2015. This review aims to critically promote quality research and focus on the building of research capacity in Australasia. .